An Empirical Study of Ethical leadership and Ethical Climate towards Corporate Social Responsibility: Pakistan Telecommunication Company Limited (PTCL) - Pirzada, Mian Jamal Uddin (ELITE JOURNAL, 2023)
Purpose: In recent era repeatedly growing demand for Ethical values in the competitive market, in this context Ethical Leadership has been playing a critical role to promote pro environmental behavior and ethical perspective. Based on Social learning theory and social exchange theory, this research evaluating the effect of ethical leadership and ethical climate on corporate social responsibility. Significant key feature of this research was that to examine the effect of ethical leadership and ethical climate on CSR. Approach/Design: To analyze the hypothesis of this research, data were collected from four capital cities (Sindh, Punjab, and Baluchistan) more than 300 employees were involved in research survey who are currently worked in PTCL (Pakistan Telecommunication Company Limited). Findings: In this study hypothesis tested, the result of 300 employees working in PTCL, results showed that the positive association between Ethical Leadership and CSR, Ethical Climate and CSR with two different combinations. However, it was noticed that ethical leadership and ethical climate both are directly influence on CSR with significant effect. Research implications/Limitations: The initial research limitations based on data, which has collected from four different headquarters (Karachi, Lahore, Quetta, Peshawar) of PTCL in Pakistan. Results of this research just focus on four cities and only one organization, so the rest of cities and other telecom companies not including in this research. Practical implications: This study highlighted the importance of Ethical leader who positively influence on Ethical climate, it is also play a vital role as a CEO or manager to motivate employees for ethical duties and social responsibilities. It was suggested that top management specifically CEO’s and MDs were involved to develop ethical climate in the organization that reflect and promote pro-social behavior in the shape of corporate social responsibility. Keywords, (Ethical Leadership, Ethical Climate, Corporate Social Responsibility, Social Exchange theory, Social Learning theory).